2018
DOI: 10.18176/jiaci.0212
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunotherapy With Egg and Milk: Changes in Peripheral Serum Cytokines Are Not Predictive Factors for Severe Adverse Reactions or for the Final Report

Abstract: Introduction: Oral immunotherapy (OIT) is a new approach in patients with food allergy. Various immunological mechanisms underlie the reversal of food allergy. In this paper, we study possible changes in peripheral cytokine patterns during OIT. Methods: Determinations of cytokines in peripheral blood were made in children who had milk or egg allergy and who received OIT. The determinations were made before and after OIT, and again following a final repeat oral challenge a month after a diet excluding the culpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For both egg and milk OIT, Garcia-Lirio et al noted the serum cytokine levels (IL-2, IL-4, IL-6, IL-10, IL-12, IL-17, IFNγ, and TNFα) did not change during OIT and therefore could not predict those patients who might be at greater risk of persistent reactions [35]. Unfortunately, the authors did not assess cytokine response of peripheral blood mononuclear cells following in vitro allergen stimulation.…”
Section: Patient-related Factors (A) Eggmentioning
confidence: 99%
“…For both egg and milk OIT, Garcia-Lirio et al noted the serum cytokine levels (IL-2, IL-4, IL-6, IL-10, IL-12, IL-17, IFNγ, and TNFα) did not change during OIT and therefore could not predict those patients who might be at greater risk of persistent reactions [35]. Unfortunately, the authors did not assess cytokine response of peripheral blood mononuclear cells following in vitro allergen stimulation.…”
Section: Patient-related Factors (A) Eggmentioning
confidence: 99%
“…Our report is not a controlled trial useful to understand the mechanisms, the evolution of sIgE, or the factors that predict failure/success [3,[13][14][15][16], but a description of the clinical response in real life over the long term. Some authors do not recommend DSZ as a routine procedure [2], but in the meantime, children with severe allergies are at high risk of reactions and even death.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 13 observational studies [60][61][62][63][64][65][66][67][68][69][70][71][72] (582 participants, with an avoidance period ranging from 2 to 8 weeks) with relevant data. Out of the cohort studies, only 4 reported usable data for both the intervention arms.…”
Section: Desensitization To More Than 5 ML Of Milk After An Avoidance...mentioning
confidence: 99%